Digitalisasi Pengelolaan Kunjungan Tamu Melalui Visitor Tracking & Management System pada Pengadilan Agama Jambi - Elvi Yanti (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2026)
Managing guests or visitors at public service institutions such as the Jambi Religious Court still faces various challenges when done manually using a guestbook, including inconsistent record-keeping, difficulty in tracking visit history, a lack of notifications to the designated staff members, and insufficient data for service reporting and evaluation. This study aims to design and develop a web-based Visitor Tracking & Management System (VTMS) application capable of digitizing the entire visitor visit process from registration, queuing, and call-ups to meetings and the completion of service accompanied by automatic notifications to the designated staff via a WhatsApp Gateway. The system development method uses the Waterfall model, which includes the stages of requirements analysis, database and interface design, implementation, and testing. The database design is illustrated through an Entity-Relationship Diagram (ERD) consisting of eight main entities: visitor, employee, user, unit, visit_type, wa_log, activity_log, and settings. The research resulted in a web-based application that provides modules for a visitor statistics dashboard, master data (users, work units, employees, visit types), visitor registration, queue and visit status management, WhatsApp notification integration, as well as visit reports that can be filtered and exported. This application is expected to improve the efficiency, security, and accountability of visitor services at the Jambi Religious Court.